Rencana Pengembangan Lanskap Agrowisata Di Kawasan Bukit Piantus Sejangkung - SABAHAN, SABAHAN; DARMANSYAH, ERIK (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Landscape Development Plan Agrotourism in Piantus Hill Area, Sejangkung District This study aims to create an agrotourism development in the Piantus Hill area. This study is limited to the planning department for agrotourism. The planning process includes the preparation of studies, concepts, data collection, analysis, synthesis, and planning of agro-tourism area. Data taken the form of primary and secondary data were analyzed descriptively and spatially. The concept of planning in this research is to develop a community-based agrotourism area. The concept was developed into the concept of landscape space, circulation, and activities. Space was developed following the existing site conditions, with the creation of supporting facilities for cultural tourism activities, without losing the natural atmosphere that existed at the site so that the expected tourism activities and community life runs beiringan. The space is classified into two, namely the cultural tourism and non-tourism and culture. Circulation network developed at the site should be classified into two, namely the circulation for tourism activities (primary and sekender) and society. Tourist activities that will be developed are appropriate activities with resources pertaining to the agricultural potential of the research sites.The results of this study in the form of agro-based regional planning community to empower the potential and the resources available in the Piantus village so as to improve the welfare of local communities and to improve the satisfaction of tourists in the tour. The planned space divided into three rooms ecotourism, agrotourism supporting room, and a non agrotourism. In each room there are certain functions such as receiving, services, aquaculture, post-harvest and other space in accordance with the existing space. Activities that can be done in this agro activity can be active and passive. The planned activities are supported with adequate facilities that include agro tourism facilities and service facilities. Moreover, the addition of utilities such as water, electricity, sewage treatment and waste, and communication and promotion will further strengthen the presence of agrotourism in the Piantus Hill area future.